Agroindústria canavieira e emprego: evolução recente e perspectivas - Lima, Débora Juliene Pereira (2010)
This study was designed to analyze the socioeconomic impacts of the process of mechanization of sugarcane sector and the expansion of production in new areas like the Midwest. The sugar industry has expanded to new areas with emphasis on the state of Goias, however, the sugarcane industry in the Northeast region of the country stagnated, with relative loss of participation with respect to domestic production and difficulties in increasing the degree of mechanization in the light of the relief. With the introduction of new technology in sugarcane production the demand for skilled workers grows with increasing unemployment among workers with low qualification. With that, the quality and formalization of the employment rise, along with pay. A question arising from this process is about the behavior of the balance of employment. The study suggests there will be dismissal of workers involved in manual cutting, but in return there will be a greater demand for workers with higher qualification. In the end, suggests a study on alternative employment for manpower unemployed by the sector, which apparently will have no alternative work.